2015 Ieee Sensors 2015
DOI: 10.1109/icsens.2015.7370486
|View full text |Cite
|
Sign up to set email alerts
|

Highly-symmetric silicon dioxide shallow shell resonators with angstrom-level roughness

Abstract: A highly-symmetric silicon dioxide shallow shell resonator with angstrom-level roughness (Ra=4.3Å) is presented. Curvature discontinuities in shallow shells, at a controlled distance from the base anchor of the shell, provide acoustic decoupling and significantly reduce the anchor contribution to the frequency split in degenerate wineglass modes as well as their damping. The Finite Element Method (FEM) simulations, performed in COMSOL 4.4, show increasing strain energy density at the vicinity of curvature disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In CVGs, the resonating mass acts as the main sensing element and the geometry of it can be of different shapes. Based on the resonating mass, these types of gyroscopes can be in the form of a string [ 4 ], a single beam [ 5 , 6 ], U-shaped tuning forks (two parallel beams) [ 7 , 8 , 9 ], rocking-mass gyroscope systems (two perpendicular in-plane beams) [ 10 , 11 ], a butterfly [ 12 , 13 ], disks [ 14 , 15 , 16 , 17 , 18 , 19 ], cloverleaf-type disks [ 20 ], rings [ 21 , 22 , 23 ], rings with compliant spokes [ 24 ], non-continuous double rings (called folded-beam disks) [ 25 ], disks with special forms of supporting beams (called honeycomb disks) [ 26 ], cylinders [ 27 , 28 , 29 , 30 , 31 ], cupped cylinders [ 32 ], bell-shapes [ 33 , 34 , 35 ], 3D rectangular parallelepiped gyroscopes based on special vibratory modes of solid material (e.g., thickness-shear vibrating mode) [ 36 , 37 ], pierced shallow shells [ 38 ], shallow shells [ 39 ], microbubbles (spherical caps with a radius-over-height ratio larger than one) [ 40 ], cennospheres (hollow spheres) [ 41 ], quasi-spherical forms [ 42 ], spherical shell resonator gyroscopes [ 43 , 44 ,…”
Section: Introductionmentioning
confidence: 99%
“…In CVGs, the resonating mass acts as the main sensing element and the geometry of it can be of different shapes. Based on the resonating mass, these types of gyroscopes can be in the form of a string [ 4 ], a single beam [ 5 , 6 ], U-shaped tuning forks (two parallel beams) [ 7 , 8 , 9 ], rocking-mass gyroscope systems (two perpendicular in-plane beams) [ 10 , 11 ], a butterfly [ 12 , 13 ], disks [ 14 , 15 , 16 , 17 , 18 , 19 ], cloverleaf-type disks [ 20 ], rings [ 21 , 22 , 23 ], rings with compliant spokes [ 24 ], non-continuous double rings (called folded-beam disks) [ 25 ], disks with special forms of supporting beams (called honeycomb disks) [ 26 ], cylinders [ 27 , 28 , 29 , 30 , 31 ], cupped cylinders [ 32 ], bell-shapes [ 33 , 34 , 35 ], 3D rectangular parallelepiped gyroscopes based on special vibratory modes of solid material (e.g., thickness-shear vibrating mode) [ 36 , 37 ], pierced shallow shells [ 38 ], shallow shells [ 39 ], microbubbles (spherical caps with a radius-over-height ratio larger than one) [ 40 ], cennospheres (hollow spheres) [ 41 ], quasi-spherical forms [ 42 ], spherical shell resonator gyroscopes [ 43 , 44 ,…”
Section: Introductionmentioning
confidence: 99%
“…Another study also reported an MEMS diamond hemispherical resonator that was fabricated by isotropically etching the glass (Corning 1715) as the hemispherical mould [8]. An Si dioxide shell resonator is presented in [9, 10] and a polySi microhemispherical resonating gyroscope is reported in [11, 12]. The material of Invar‐36 is also used to fabricate microhemispherical shell resonator in [13].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, most microhemisphere shell resonators studied were fabricated without the integrated electrodes. Many researches did not fully construct sensing and driving units for functioning resonating structures [4][5][6][7][8][9][10]. These approaches are limited by the lack of functional electrode structures with controllable capacitive gaps.…”
mentioning
confidence: 99%